1998
DOI: 10.1180/000985598545354
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of North Sea Tertiary mudrocks: investigations by triaxial testing of side-wall cores

Abstract: In the North Sea Tertiary section, wellbore instability problems are frequently reported in Palaeocene-Early Oligocene smectite-rich mudrocks. Analysis of the mechanical properties of these Tertiary mudrocks is generally hampered by the lack of suitable core material. This study represents an attempt to study the geomechanical behaviour of mudrocks by triaxial tests of side-wall cores obtained from the borehole wall. The tests performed include measuring the changes in pore pressure during shearing and undrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Marsden et al (1992) noted some correspondence between smectite content, cation exchange capacity, specific surface area and strength in a study of weak mudrocks under high stress levels but noted no such correlation for porosity or velocity. Steiger and Leung (1988), Nakken et al (1989), Ewy et al (1994), Wensaas et al (1998) and Nygard and Gutierrez (2002) also observed a correlation between smectite content and rock strength. Ingram and Urai (1999) developed the following correlation for shale friction angle (f) from specific surface area (SSA) obtained using the dielectric constant method:…”
Section: Previous Workmentioning
confidence: 81%
See 1 more Smart Citation
“…Marsden et al (1992) noted some correspondence between smectite content, cation exchange capacity, specific surface area and strength in a study of weak mudrocks under high stress levels but noted no such correlation for porosity or velocity. Steiger and Leung (1988), Nakken et al (1989), Ewy et al (1994), Wensaas et al (1998) and Nygard and Gutierrez (2002) also observed a correlation between smectite content and rock strength. Ingram and Urai (1999) developed the following correlation for shale friction angle (f) from specific surface area (SSA) obtained using the dielectric constant method:…”
Section: Previous Workmentioning
confidence: 81%
“…In addition, friction coefficient is dependent on mean stress, which apparent friction at low effective normal stress much higher than friction coefficients measured at higher stresses (e.g. Marsden et al, 1992;Wensaas et al, 1998;Kågeson-Loe et al, 2004). The tests run here avoided the very low effective stress end specifically due to this phenomenon and virtually all the failure envelopes recorded in these tests were close to linear.…”
Section: Discussionmentioning
confidence: 97%
“…Rock mechanics predicts slip when the shear stresses at the fault overcome the residual shear strength. Although residual shear strengths of FIGURE 13 | (A) Mohr circles of effective stresses for burial under earth pressure at rest (K 0 ) relative to Coulomb failure envelope based on current mechanical properties of the lower Hordaland Group (Wensaas et al, 1998); (B) Mohr circles of effective stresses for burial under earth pressure at rest (K 0 ) relative to Coulomb failure envelope based on mechanical properties of "weak" clays (Moore and Lockner, 2007), as expected during shallow burial; (C) Mohr circles of effective stresses for burial for active earth pressure (K a ) relative to Coulomb failure envelope with cohesion and friction angle of the lower Hordaland Group (Wensaas et al, 1998); (D) Mohr circles of effective stresses for burial for active earth pressure (K a ) relative to Coulomb failure envelope based on mechanical properties of "weak" clays (Moore and Lockner, 2007), as expected during shallow burial; (E) Mohr circles of effective stresses for burial for earth pressure (K ′ ) relative to Coulomb failure envelope for low coefficients of residual friction (φ r ≈ 9 • ; Bishop et al, 1971).…”
Section: Fault Mechanicsmentioning
confidence: 99%
“…The coefficient of earth pressure at rest for normally consolidated clays that have not been pre-compressed or pre-sheared (Terzaghi, 1996), such as the mudstones of the Hordaland Group (Wensaas et al, 1998), can be calculated from the friction angle using Jaky's (1948) equation:…”
Section: Fault Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation